SEED DEPTH TEST AND APPLICATION OF ECO ENZYME TO THE VEGETATIVE GROWTH OF ARABICA COFFEE PLANTS (Coffea arabica) - Yudi Siswanto; Isnar Sumartono; Muhammad Wasito; Nurloza Khatimah (Yayasan Sinergi Multidimensi Kreatif, 2025)
Yudi Siswanto, Isnar Sumartono, Nurliza Khatimah. Seed Depth Test and Eco Enzyme Application to the Vegetative Growth of Arabica Coffee Plants (Coffea arabika). The purpose of this study is to determine the depth of seeds and the application of eco enzymes and their interaction with the vegetative growth of Arabica coffee plants (Coffea arabika). This research was carried out in Medan Krio Village, Sunggal District. Deli Serdang Regency. North Sumatra Province with an altitude of ± 30 meters above sea level. This research was carried out from August to November 2025. This study uses a Factorial Group Axak Design (RAK). The first factor is that the depth of the seed is given the symbol